2021
DOI: 10.3390/ijms22052398
|View full text |Cite
|
Sign up to set email alerts
|

Hopping and Flipping of RNA Polymerase on DNA during Recycling for Reinitiation after Intrinsic Termination in Bacterial Transcription

Abstract: Two different molecular mechanisms, sliding and hopping, are employed by DNA-binding proteins for their one-dimensional facilitated diffusion on nonspecific DNA regions until reaching their specific target sequences. While it has been controversial whether RNA polymerases (RNAPs) use one-dimensional diffusion in targeting their promoters for transcription initiation, two recent single-molecule studies discovered that post-terminational RNAPs use one-dimensional diffusion for their reinitiation on the same DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Among the several single-molecule assays that we established to explore the intrinsic and ρ-dependent termination mechanisms by E. coli RNAP ( 29 , 37 , 38 ), three assays were performed in this study on assorted ρ-dependent terminators, and their experimental schemes and representative results are briefed here. DNA templates each contain the T7A1 promoter and a ρ-dependent terminator, and are each labeled with biotin at the upstream end for surface immobilization and fluorescently with reddish Cy5 at the downstream end for individual real-time monitoring (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the several single-molecule assays that we established to explore the intrinsic and ρ-dependent termination mechanisms by E. coli RNAP ( 29 , 37 , 38 ), three assays were performed in this study on assorted ρ-dependent terminators, and their experimental schemes and representative results are briefed here. DNA templates each contain the T7A1 promoter and a ρ-dependent terminator, and are each labeled with biotin at the upstream end for surface immobilization and fluorescently with reddish Cy5 at the downstream end for individual real-time monitoring (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the mismatch effects may not be related to hyper-translocation but with something else. For example, a DNA region around the −12 position interacts with RNAP in the recent X-ray crystal structures 7 , 16 , and such interaction may be hypothetically important for termination.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a new mechanism of proximity-based transcription coupling was observed. Using single-molecule microscopy, Harden et al 16 and Kang et al 17,18 observed that RNAP can remain bound to DNA after termination for at least hundreds of seconds in vitro. This post-termination RNAP-DNA complex may retain a partially open bubble in the DNA 19 .…”
Section: Introductionmentioning
confidence: 99%